Design and Implementation of Digital Linear Control Systems on Reconfigurable Hardware - Marcus Bednara (EURASIP Journal on Advances in Signal Processing, 2003)
The implementation of large linear control systems requires a high amount of digital signal processing. Here, we show that reconfigurable hardware allows the design of fast yet flexible control systems. After discussing the basic concepts for the design and implementation of digital controllers for mechatronic systems, a new general and automated design flow starting from a system of differential equations to application-specific hardware implementation is presented. The advances of reconfigurable hardware as a target technology for linear controllers is discussed. In a case study, we compare the new hardware approach for implementing linear controllers with a software implementation.